The outdoor lighting of the Wawel Royal Castle and its contribution to the occurrence of light pollution - Łygan Jakub; Czaplicka Anna (Technical Transactions)
This paper concerns the phenomenon of light pollution. Its goal is to identify light sources in the Wawel Royal Castle that influence this phenomenon. The term of the discussed phenomenon is given, with emphasis on its categories. Then, the impact of light pollution on the environment was discussed. During the research, light sources were identified and divided according to their type. Then it was determined how individual light sources affect the occurrence of light pollution. The results contain information about the location of light sources, their type, colour and direction of light beam. The authors present them in photographic documentation and a map of Wawel Hill. Additionally, changes were proposed in the external lighting of the Wawel Royal Castle, aimed at reducing the occurrence of light pollution. A total of 294 light sources were inventoried, of which 82 were classified as abnormal, 59 as normal, and 63 as partially correct. The rest were unavailable or unused.